A Review of Cost-Related Research Under the Omni-channel Integration Background of Beauty Enterprises - Xu, Han (Exploring Science Academic Conference Series, 2026)
Against the backdrop of digital transformation, the online-offline omni-channel integration in the cosmetics industry has become an inevitable trend, and channel reform has profoundly reshaped enterprises’ cost structure. Taking cosmetics, omni-channel and cost as the core keywords, this paper systematically reviews relevant literature and analyzes the transmission mechanism of how omni-channel integration affects the costs of cosmetics enterprises. It focuses on four major scenarios — offline experience, live-streaming marketing, cross-channel returns, and efficacy R&D — to identify industry-specific pain points in cost control, and sorts out the corresponding cost optimization paths and empirical conclusions. The study finds that the cost logic of omni-channel operation in the cosmetics industry differs from that of general retail, and existing three-dimensional interdisciplinary research remains scarce with insufficient quantitative analysis. This paper provides theoretical reference and practical enlightenment for the cost management of cosmetics enterprises in their omni-channel transformation. Furthermore, it offers theoretical reference and practical enlightenment for the cosmetics industry to cut costs, boost efficiency across the whole industrial chain and achieve high-quality development.